Familial Henoch-Schönlein Syndrome. Issue 2 (March 2016) - Ostini, Alessandro; Simonetti, Giacomo D.; Pellanda, Giorgia; Bianchetti, Mario G.; Ferrarini, Alessandra; Milani, Gregorio P.
Abstract : Abstract: Little attention has been so far paid to familial cases of Henoch-Schönlein syndrome. We performed a search of the Medical Subject Headings terms ( Henoch or Schönlein OR anaphylactoid purpura OR IgA nephropathy OR Berger nephropathy ) AND ( family OR familial ). We identified no more than 19 reports including 47 families with a total of 100 affected cases: their ages ranged from 1.3 to 51 years (median, 11 years), with a male-to-female ratio of 1.4. Familial cases developed simultaneously in 45% and nonsimultaneously in 55% of the families. Age, male-to-female ratio, and clinical findings were not statistically different in cases with simultaneous and nonsimultaneous familial occurrence of Henoch-Schönlein syndrome. Henoch-Schönlein syndrome occurs almost always sporadically. Age at presentation, male-to-female ratio, and findings are similar in familial (both simultaneously and nonsimultaneously occurring) and sporadic Henoch-Schönlein cases.